Komparasi Kinerja Membran Ultrafiltrasi Polyvinylidene Fluoride dan Polivinyl Chloride Pada Air Sungai Jagir dalam Menurunkan TDS - Mufidah, Shafa'ul; Restu Hikmah Ayu Murti (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study aimed to evaluate the performance of PVDF and PVC ultrafiltration membranes coated with Al2O3 in removing total dissolved solids (TDS) from Sungai Jagir river water after a pre-treatment adsorption using Granular Activated Carbon (GAC). The adsorption process was conducted for 10 minutes before the water was filtered through the membranes under various operating pressures (1, 1.5, and 2 bar) and operation times (0.1–0.5 h). The results showed that both membranes exhibited an increase in TDS rejection efficiency with longer operation time, while pressure had a limited effect. The PVDF membrane demonstrated consistently higher TDS rejection compared to PVC, suggesting that membrane surface properties influence solute removal efficiency. Statistical analysis using three-way ANOVA revealed that operation time had a significant effect on TDS rejection, whereas pressure did not show a notable impact. These findings indicate that contact duration between water and membrane plays a crucial role in reducing TDS in river water through ultrafiltration.